Complicated Lymphogranuloma Venereum With Pelvic Peritonitis in Young Man. Issue 6 (November 2017) - Pasquer, Arnaud; Fanget, Florian; Djeudji, Filbert; Coppere, Brigitte; Boibieux, Andre; Barth, Xavier
Abstract : Abstract: Chlamydia trachomatis –linked pelvic peritonitis occurs mainly in young women of childbearing age, most often in a context of salpingitis. Fitz-Hugh–Curtis syndrome and perihepatitis have been reported in only 2 men with acquired immunodeficiency syndrome. We present here the observation of these patients including clinical presentation, morphological examinations, and therapeutic decision with follow-up. No surgery was performed. Antibiotic therapy was successfully introduced. Chlamydia trachomatis –linked pelvic peritonitis rarely occurs in men and is often associated to immunodeficiency. Diagnosis must be evoqued in medical peritonitis with no etiology found when patient's anamnesis tends to suspect an important sexually transmitted disease risk. Abstract : Chlamydia trachomatis -linked pelvic peritonitis occurs mainly in young women of childbearing age, most often in a context of salpingitis. Fitz-Hugh-Curtis syndrome and peri-hepatitis has been reported in only 2 males with AIDS. The authors report a case of pelvic peritonitis linked to C. trachomatis in a 25-year-old man, detailing the clinical aspects, diagnosis, and therapy of this rare presentation.